Information Interchange Layer based on Classification of Information Use (IU) - Albarda Albarda; Suhono Harso Supangkat; Kuspriyanto Kuspriyanto; Jaka Sembiring (Universitas Ahmad Dahlan, 2014)
Information characteristics in classification of IU directly related to aspects of information usage by user in enterprise to accomplish their activities. Feature extraction from information usage in three layer of enterprise management used as parameter for this characteristic. Characteristics and dimension applied to develop middle-ware system (called Information Interchange Layer) that bridges a common issue ie information silo, to optimize a services of information resources in enterprise